A Newborn with Congenital Glucose-Galactose Malabsorption and Recurrent Episodes of Sepsis - Serdar Alan; Zarife Kuloğlu; Ufuk Çakır; Aytaç Yaman; Begüm Atasay; Aydan Kansu Tanca; Saadet Arsan (Güncel Pediatri, 2013)
Congenital glucose-galactose malabsorption is a chronic osmotic diarrhea due to defective absorption of glucose and galactose in the intestine. Here, we present a newborn that was admitted to our hospital for neonatal diarrhea and was diagnosed as congenital glucose-galactose malabsorption. He had recurrent sepsis with Candida albicans, Klebsiella pneumoniae and Enterococcus faecalis during follow-up without having any underlying cellular or humoral immune deficiency.Early diagnosis and appropriate treatment of this rare disease can prevent life-threatening complications, and normal growth and development can be achieved. To our knowledge, the present case will be the second glucose-galactose malabsorption case with recurrent infectious due to opportunistic microorganisms after only one similar case in the literature. (Journal of Current Pediatrics 2013;11:85-7)